PMO-183 Role of IL28B polymorphism in prediction of response to therapy in patients with genotype 1 chronic hepatitis c infection. (28th May 2012) - Mustafa, Z; Gaffney, D; Matthews, E; Barclay, S; Priest, M; Spooner, R; Mills, P R
Abstract : Introduction: Patients with chronic hepatitis C virus (HCV) infection have a variable response to antiviral therapy with pegylated interferon and ribavirin. Influences include age, gender, viral genotype, viral load, severity of liver disease and coinfection. Around 45% of patients with viral genotype 1(G1) infection respond compared with 70%–80% with genotype 2/3. Recently a human IL28B polymorphism has been found to predict response in patients with G1 infection. There is little data on this from Europe and a study of IL28B polymorphisms in patients with G1 infection treated in Glasgow was conducted. Methods: Sequential Caucasian patients with G1 chronic HCV who had been treated with combination antiviral therapy were studied. Responses were classified as sustained viral response (SVR), relapse (R) or non-responder (NR). None had coinfection. Data on age, gender, viral load, duration of therapy and severity of liver disease (Ishak fibrosis stage <4 or ≥4) were collected. Individuals were genotyped for IL28B polymorphism rs12979860 using TaqMan ®, Drug Metabolism Genotyping Assays and reported as CC, CT or TT. Results: 63 patients were classified (number, mean age, females, advanced fibrosis) by treatment response as SVR (18, 44, 4, 1), R (20, 46, 8, 8) and NR (25, 46.4, 4, 10). Mean pre-treatment viral load was similar in the three groups (5.2, 5.4, 5.8 log10 IU/ml) and mean duration of therapy shorter for NR (46.2, 47.2, 8.4 weeks) who often fulfilled an early stopping rule. The IL28B genotype was highly predictive of response (Abstract PMO-183 table 1 ). CC individuals have a much greater likelihood (p<0.002) of being in the SVR group than CT or TT individuals. Poorer response was also seen in patients with advanced fibrosis. Conclusion: The IL28B polymorphism is a useful and cheap assay allowing some prediction of response to antiviral therapy in patients with G1 chronic HCV infection. Competing interests: None declared.